Progesterone prevents impairment of cognitive, affective and motor events in a reserpine model of parkinsonism in male rats - Yunes, Roberto Miguel Federico (2022)
Parkinson’s is a common neurodegenerative disorder, second only to Alzheimer´s disease.It has been the object of growing interest since its frequency tends to augment as life expectancyhas increased globally considered. In this work, we study the eventual neuroprotective effect ofProgesterone (P4) injected a few days before establishing a Reserpine (R) model of Parkinsonism inadult male rats. We focused on cognitive (Novel Object Recognition test; NOR), affective (ForcedSwimming Task; FST) and motor (Catalepsy Test; CT) outputs. We performed the appropriate testsalong with the administration for two weeks of low doses of R. Our results show very clearly thatP4 prevents the impairment of several tasks regarding the deleterious effects of R, without affectingnegatively other areas of the subject behavior. In total accordance with current information, weshow here that P4 -in particular- and neuroactive steroids -in general- are promising molecules todelay diverse manifestations of neurotransmitters depletion.